Desperate living [videorecording (DVD)] - Waters, John, 1946-; Waters, John, 1946-; Renay, Liz; Stole, Mink; Lowe, Susan, 1948-; Massey, Edith; Pearce, Mary Vivian (Warner Bros. Home Entertainment, 2017)
Things get rocky at the Gravel household when paranoid Peggy Gravel and her murderous maid, Grizelda, kill Peggy's husband. They escape from the law, only to wind up in the crazy town of MorTVille, where Queen Carlotta presides over a sleazy collection of misfits, including the vivacious Muffy St. Jacques. When the queen disinherits her daughter, Princess Coo-Coo, the citizens of MorTVille decide that it's time for a few changes.